Self-Medication Practices in Remote, Border, and Island Areas: A Literature Review - Tya Palpera Utami; Najmah Najmah; Haerawati Haerawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Health is defined as a state of physical, mental, and social well-being that enables every individual to lead a socially and economically productive life. One of the initial efforts in treatment is the practice of self-medication. Self-medication is the independent use of medication without supervision or direct consultation with a health professional, with the aim of addressing health complaints experienced. The purpose of this study was to examine the description and risk factors of self-medication in Indonesia and globally. This research method is a descriptive observational study using a literature review design, with the following databases: Wiley Online Library, PubMed, and ScienceDirect From 2021 to 2025, a total of 25 articles were reviewed. The search strategy for articles in Wiley Online Library, PubMed, Google Scholar, and ScienceDirect used four keywords: